1998
DOI: 10.1172/jci4814
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular endothelial cell growth factor in Ovarian Hyperstimulation Syndrome.

Abstract: Controlled ovarian hyperstimulation with gonadotropins is followed by Ovarian Hyperstimulation Syndrome (OHSS) in some women. An unidentified capillary permeability factor from the ovary has been implicated, and vascular endothelial cell growth/permeability factor (VEGF) is a candidate protein. Follicular fluids (FF) from 80 women who received hormonal induction for infertility were studied. FFs were grouped according to oocyte production, from group I (0-7 oocytes) through group IV (23-31 oocytes). Group IV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(27 citation statements)
references
References 50 publications
1
24
0
2
Order By: Relevance
“…In the present study, we also showed that ZO-1 protein levels in endothelial cells incubated with FF from OHSS patients were lower than those of the control group. These results are consistent with those obtained by Levin et al (1998), who showed that FF from patients suffering from severe OHSS induces destruction of the endothelial ZO-1 TJ protein. We found no changes in ZO-1 levels after the pre-incubation of FF from women at risk of OHSS with the ANGPT1-neutralising antibody.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we also showed that ZO-1 protein levels in endothelial cells incubated with FF from OHSS patients were lower than those of the control group. These results are consistent with those obtained by Levin et al (1998), who showed that FF from patients suffering from severe OHSS induces destruction of the endothelial ZO-1 TJ protein. We found no changes in ZO-1 levels after the pre-incubation of FF from women at risk of OHSS with the ANGPT1-neutralising antibody.…”
Section: Discussionsupporting
confidence: 93%
“…Endothelial Cell Permeability Assay-Assays were performed as described previously (9). Primary cultures of BAEC were seeded onto 0.45-m CM filters (Millipore, Bedford, MA) within plastic inserts; the inserts were placed into 24-well plates, and the cells were grown to confluence over several days.…”
Section: Methodsmentioning
confidence: 99%
“…This permeability factor also modulates the formation and function of vesiculovascular organelles in venules (5) and the development of EC fenestrations (6). These mechanisms underlie the enhanced vascular permeability seen in response to VPF, which is implicated in the ascites associated with ovarian and other carcinomas (1,7), the pathogenesis of diabetic retinopathy (8), and the ovarian hyperstimulation syndrome (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations